Research on the optimisation of flight landing scheduling with multi-runway. (2018) - Peng, Yunfang; Tang, Qing; Han, Yajuan
Flight scheduling is the foundation and core of all the activities of airports and airlines. This paper analyses the problem of flight landing scheduling with multi-runway and establishes mathematical model. The aim is to determine the aircraft landing sequence and the landing time with the objective to minimise the landing time deviation cost. A new heuristic approach called cost decision algorithm (CDA) is present to solve the problem. This method selects the runway and decides the landing time by comparing the costs. With a series of experiments of different scale data, the mathematical model is solved by CDA and other algorithm. The computational results demonstrated the feasibility and superiority of the proposed algorithm by comparing with other algorithms in solutions and running time.